2019
DOI: 10.1111/nyas.14190
|View full text |Cite|
|
Sign up to set email alerts
|

Fucoidan affects oral squamous cell carcinoma cell functions in vitro by regulating FLNA‐derived circular RNA

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most common cancer types, with a high annual incidence. Although chemotherapy contributes to suppressing OSCC tumorigenesis, the available treatments result in poor prognosis because of local recurrence and regional lymph node metastasis. Thus, it is necessary to discover novel and safe drugs with greater effectiveness and fewer side effects. Fucoidan is a component of the cell wall of brown seaweed that has been shown to produce a wide range of biological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…CircRNAs play important roles in the carcinogenesis and development of many cancers [27]. Among the researched circRNAs, only circFLNA was reported to be abnormally expressed in human oral and laryngeal squamous cell carcinomas [28][29][30]. In this study, The level of cleaved caspase-3/caspase-3 was analyzed quantitatively in the tissues from mice injected with A549 cells.…”
Section: Discussionmentioning
confidence: 93%
“…CircRNAs play important roles in the carcinogenesis and development of many cancers [27]. Among the researched circRNAs, only circFLNA was reported to be abnormally expressed in human oral and laryngeal squamous cell carcinomas [28][29][30]. In this study, The level of cleaved caspase-3/caspase-3 was analyzed quantitatively in the tissues from mice injected with A549 cells.…”
Section: Discussionmentioning
confidence: 93%
“…reported that circFLNA is a fucoidan target. They found that fucoidan increased the expression of circFLNA in OSCC cell lines and affected the expression of key proteins related to growth, apoptosis, migration, and invasion ( 39 ).…”
Section: Circrnas Are Widely Expressed and Serve As Markers And Targets In Hncmentioning
confidence: 99%
“…The analysis of glycosidic bonds showed that (1,3)-α-1-ethyl fuco-pyranose (31.9%) was the main residue, followed by 1,2-linked (13.2%) and 1,4-linked (7.7%) fucose and highly branched (22.4%). A large number of studies have shown that fucoidan induces cytotoxicity towards various types of cancer cell, induces apoptosis and inhibits the invasion, metastasis and angiogenesis of cancer cells [48][49][50][51][52][53][54][55][56][57][58]. Damonte et al discussed the structure of alginate in detail along with its biological functions in the mechanisms of apoptosis, invasion, metastasis, angiogenesis and the growth and signaling of cancer cell growth, which proved the medicinal value of these alginoglycans [59].…”
Section: Structure and Characteristics Of Other Seaweed Polysaccharidesmentioning
confidence: 99%